An oocyte-specific ELAVL2 isoform is a translational repressor ablated from meiotically competent antral oocytes - Chalupnikova, Katerina; Solc, Petr; Sulimenko, Vadym; Sedlacek, Radislav; Svoboda, Petr (Cell Cycle, 2014)
At the end of the growth phase, mouse antral follicle oocytes acquire full developmental competence. In the mouse, this event is marked by the transition from the so-called non-surrounded nucleolus (NSN) chromatin configuration into the transcriptionally quiescent surrounded nucleolus (SN) configuration, which is named after a prominent perinucleolar condensed chromatin ring. However, the SN chromatin configuration alone is not sufficient for determining the developmental competence of the SN oocyte. There are additional nuclear and cytoplamic factors involved, while a little is known about the changes occurring in the cytoplasm during the NSN/SN transition. Here, we report functional analysis of maternal ELAVL2 an AU-rich element binding protein. Elavl2 gene encodes an oocyte-specific protein isoform (denoted ELAVL2°), which acts as a translational repressor. ELAVL2° is abundant in fully grown NSN oocytes, is ablated during the NSN/SN transition and remains low during the oocyte-to-embryo transition (OET). ELAVL2° overexpression during meiotic maturation causes errors in chromosome segregation, indicating the significance of naturally reduced ELAVL2° levels in SN oocytes. On the other hand, during oocyte growth, prematurely reduced Elavl2 expression results in lower yields of fully grown and meiotically matured oocytes, suggesting that Elavl2 is necessary for proper oocyte maturation. Moreover, Elavl2 knockdown showed stimulating effects on translation in fully grown oocytes. We propose that ELAVL2 has an ambivalent role in oocytes: it functions as a pleiotropic translational repressor in efficient production of fully grown oocytes, while its disposal during the NSN/SN transition contributes to the acquisition of full developmental competence.
Keywords: Animals; myši transgenní; Female; buněčné linie; ELAV-Like Protein 2; Meiosis; Mice, Transgenic; ženské pohlaví; meióza; Oocytes; ovariální folikul; lidé; Gene Knockdown Techniques; oocyty; Mice, Inbred BALB C; Cell Line; Male; myši inbrední BALB C; Protein Isoforms; genový knockdown; protein - isoformy; zvířata; mužské pohlaví; Mice, Inbred C57BL; Ovarian Follicle; ELAV-like protein 2; myši inbrední C57BL; Humans